Biomechanical properties of masticatory balance in cases with RPDs: the influence of preferred and nonpreferred chewing side : a pilot study - Eberhard, Lydia; Rues, Stefan; Bach, Lea; Lenz, Jürgen; Schindler, Hans J. (Clinical and experimental dental research, 2022)
Objectives Removable partial dentures (RPDs) are inserted with the aim to restore masticatory function. There is however inconsistent evidence supporting the alleged improvements, posterior occlusal contacts being one of the decisive factors. We hypothesized that the distribution of abutment teeth in RPDs influences masticatory performance and functional parameters. To evaluate the masticatory performance and functional parameters in patients with a RPD using a single mathematical parameter (tilting index [TI]) for both jaws that predicts biomechanical behavior on the basis of the distribution of abutment teeth. Materials and Methods Masticatory performance was measured in patients wearing long-time adapted RPDs using the standardized test food optocal, yielding the mean particle size (X50). Mastication on the preferred and nonpreferred chewing sides was analyzed. Total muscle work (TMW) was calculated using bipolar electromyographic recordings of the masseter and anterior temporalis muscle. Functional parameters were subjected to multiple linear regression analysis including X50 as a dependent variable and functional units (FU), the number of teeth, bite forces, and sagittal and frontal components of TI (TI α and TI β) as independent variables. Results When the preferred chewing side was tested, none of the investigated parameters correlated significantly with X50. In contrast, chewing on the nonpreferred side was correlated significantly with performance for most variables (p < .05). This means that increased dental support improved chewing performance with RPDs under these conditions. Conclusions In well-adapted RPDs, the distribution of abutment teeth as expressed by the tilting index seems to be of subordinate importance for masticatory performance.
Gesehen am 05.12.2022